Analysis of Patient Safety Management in Committee for Quality Improvement and Patient Safety at Sumbawa Hospital, West Nusa Tenggara - Evie Sulahyuningsih; Didik Gunawan Tamtomo; Hermanu Joebagio (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Patient safety is a crucial issue and a focus of policy standard in internationally accredited organizations. The specific committee responsible for quality improvement in patient safety is the committee for quality improvement and patient safety (PMKP). Incidence of malpractice often occurs but are not reported. It indicates that the committee has not worked according to required accreditation standard. This study aimed to analyze patient safety management with the committee for quality improvement and patient safety at Sumbawa Hospital, West Nusa Tenggara. Subjects and Method: This was a qualitative study with phenomenology approach. Nine study participants were selected purposively, consisting of 3 committee members (chairperson, secretary, and patient safety sub-committee), 3 chiefs of ward (pediatrics, internal medicine, and surgery), and 4 nurses or midwives (pediatrics, surgery, ICU/ICCU, and obstetrics).Results: The committee for quality improvement and patient safety has been established at Sumbawa Hospital, West Nusa Tenggara to meet the requirement of hospital accreditation standard. It aimed to improve the quality of services and to assure patient safety. However, its work has not meet the required standard. The lack of knowledge among involving parties, including hospital management, PMKP member, medical professionals was identified as one important obstacle for the implementation of patient safety management. This has led to the incidence of malpractice at the hospital, sub-standard quality of services and patient safety.Conclusion: PMKP has been established at Sumbawa Hospital, West Nusa Tenggara. However, their work have not meet the required standard. The lack of knowledge among involving parties, including hospital management, PMKP, and health professional, has led to the incidence of malpractice at the hospital, sub-standard quality of services and patient safety.Keyword: quality improvement, patient safety management, committeeCorrespondence: Evie Sulahyuningsih. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Mobile: 08786410495.Journal of Health Policy and Management (2017), 2(2): 147-156https://doi.org/10.26911/thejhpm.2017.02.02.06